Dense genotyping of immune-related loci identifies HLA variants associated with increased risk of collagenous colitis. Issue 3 (2nd November 2015) - Westerlind, Helga; Mellander, Marie-Rose; Bresso, Francesca; Munch, Andreas; Bonfiglio, Ferdinando; Assadi, Ghazaleh; Rafter, Joseph; Hübenthal, Matthias; Lieb, Wolfgang; Källberg, Henrik; Brynedal, Boel; Padyukov, Leonid; et al.
Abstract : Objective: Collagenous colitis (CC) is a major cause of chronic non-bloody diarrhoea, particularly in the elderly female population. The aetiology of CC is unknown, and still poor is the understanding of its pathogenesis. This possibly involves dysregulated inflammation and immune-mediated reactions in genetically predisposed individuals, but the contribution of genetic factors to CC is underinvestigated. We systematically tested immune-related genes known to impact the risk of several autoimmune diseases for their potential CC-predisposing role. Design: Three independent cohorts of histologically confirmed CC cases (N=314) and controls (N=4299) from Sweden and Germany were included in a 2-step association analysis. Immunochip and targeted single nucleotide polymorphism (SNP) genotype data were produced, respectively, for discovery and replication purposes. Classical human leucocyte antigen (HLA) variants at 2-digit and 4-digit resolution were obtained via imputation from single marker genotypes. SNPs and HLA variants passing quality control filters were tested for association with CC with logistic regression adjusting for age, sex and country of origin. Results: Forty-two markers gave rise to genome-wide significant association signals, all contained within the HLA region on chromosome 6 (best p=4.2×10 −10 for SNP rs4143332). Among the HLA variants, most pronounced risk effects were observed for 8.1 haplotype alleles including DQ2.5, which was targeted and confirmed in the replication data set (p=2.3×10 −11 ; OR=2.06; 95% CI (1.67 to 2.55) in the combined analysis). Conclusions: HLA genotype associates with CC, thus implicating HLA-related immune mechanisms in its pathogenesis.